Stakeholders perspectives on unaccompanied minors - Roberto, S.; Moleiro, C.; Lemos, L. (Journal of Constructivist Psychology, 2021)
In 2017 it was estimated that there were more than 60 million refugees worldwide, half of whom were children, including unaccompanied minors. The characteristics of unaccompanied minors have been relatively understudied, and it is recognized that there is the need for systematic knowledge to support the intervention being carried out with this group at an European level. This article presents the results of a research project aimed to characterize the reception and host contexts of unaccompanied minors in Portugal. Twenty semi-structured interviews with stakeholders were conducted regarding their understanding of who unaccompanied minors are and what is the type of adequate intervention with this group. The interviews revealed three main perspectives: a) the vulnerability of young asylum seekers; b) the agency within the migratory project; c) the non-differentiation from other children and young people at risk. These findings are important to systematize and share knowledge for the improvement and optimization of public policies regarding unaccompanied minors.